Effect of Schizochytrium limacinum supplementation to a low fish-meal diet on growth performance, lipid metabolism, apoptosis, autophagy and intestinal histology of Litopenaeus vannamei - Yao, Xinzhou; Lin, Yingying; Shi, Menglin; Chen, Liutong; Qu, Kangyuan; Liu, Yucheng; Tan, Beiping; Xie, Shiwei (Frontiers in Marine Science, 2022)
In this experiment, we aimed to evaluate the relationship between the addition of Schizochytrium limacinum to low fish meal diets on growth performance, apoptosis, autophagy, lipid metabolism, and intestinal health of Lipenaeus vanamei. The diet containing 25% fish meal was used as a positive control (FM) and the other three diets contained 15% fish meal and were supplemented with 0, 0.3, and 0.6% S. Limacinum (LF, LFLD, LFHD). The shrimp (0.22 ± 0.00 g) were divided into four replicates of 40 shrimp per tank and fed four times daily to apparent satiation for 8 weeks. Results showed that the final weight (FBW) and weight gain rate (WGR) of shrimp fed FM and LFHD diets were significantly increased compared to those fed the LFLD diet (P<0.05), and there was no significant difference in survival rate (SR) and feed conversion rate (FCR) among the groups (P>0.05). Supplementation of S. Limacinum in low fish meal diets had no effects on shrimp body composition (P<0.05). There were significant differences (P<0.05) in low-density lipoprotein (LDL-C) glucose (GLU), triglycerides (TG), and total cholesterol (TC) in the hemolymph of shrimp fed the LF diet compared to those fed the LFLD and LFHD diets. HE staining and transmission electron microscopy (TEM) results showed that the microvilli height, mucosal folds height, mucosal folds width and muscle layer thickness in the intestine of shrimp fed the LF diet were significantly reduced compared to those fed the other three diets (P<0.05). Swelling of the endoplasmic reticulum and irregular mitochondria in the gut of shrimp fed the LF diet was also observed by TEM, and the endoplasmic reticulum and mitochondria of shrimp fed the LFHD diet returned to a healthy state. Hepatopancreas genes expression results were showed that the gene expression of 5′ -AMP-activated protein kinase (ampk), stearoyl-CoA desaturase (scd1), acetyl-CoA carboxylase 1 (acc1), and malonyl-CoA decarboxylase (mcd) of shrimp fed the LF diet was significantly increased compared to those fed the FM diet (P<0.05). The gene expression of sterol regulatory element-binding protein (srbep) and carnitine palmitoyl transferase 1 (cpt-1) of shrimp fed the LFLD diet was significantly increased compared to those fed the LF diet (P<0.05). The gene expression of acc1, mcd and scd1 of shrimp fed the LFHD diet was significantly reduced compared to those fed the LF diet (P<0.05). Results of genes expression associated with apoptosis in the hepatopancreas showed that the gene expression of B lymphocytoma-2 (bcl-2), BCL2 associated X apoptosis regulator (bax) and cysteinyl aspartate specific proteinase 8 (caspase 8) of shrimp fed the LF diet was significantly reduced compared to those fed the FM diet (P<0.05). The gene expression of bcl-2 of shrimp fed the LFHD diet was significantly reduced compared to those fed the LF diet (P<0.05). Genes related to autophagy in the hepatopancreas showed that the expression of autophagy-related protein 12 (atg 12), autophagy-related protein 13 (atg 13) and beclin1 of shrimp fed LF the diet was significantly reduced compared to those fed the FM diet (P<0.05). The gene expression of atg 12 and atg 13 of shrimp fed the LFHD diet was significantly increased compared to those fed the LF diet (P<0.05). In summary, reducing fish meal is detrimental to the growth performance and intestinal health of shrimp, and 0.6% S. Limacinum supplementation can improve the growth performance, promotes hepatopancreas lipid metabolism, reduces apoptosis, promotes autophagy and improve intestinal health of Litopenaeus vannamei.